Microsoft Copilot - Minnick, Chris (--For dummies., 2025)
Microsoft is enhancing all its most widely used productivity software--including Windows and apps like Word and Excel--with the power of AI. And now you can learn to make the most of this revolutionary new tool with Microsoft Copilot For Dummies!